2020
DOI: 10.1186/s13045-020-00863-9
|View full text |Cite
|
Sign up to set email alerts
|

An Auristatin nanoconjugate targeting CXCR4+ leukemic cells blocks acute myeloid leukemia dissemination

Abstract: Background: Current acute myeloid leukemia (AML) therapy fails to eliminate quiescent leukemic blasts in the bone marrow, leading to about 50% of patient relapse by increasing AML burden in the bone marrow, blood, and extramedullar sites. We developed a protein-based nanoparticle conjugated to the potent antimitotic agent Auristatin E that selectively targets AML blasts because of their CXCR4 receptor overexpression (CXCR4+) as compared to normal cells. The therapeutic rationale is based on the involvement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 46 publications
1
48
0
Order By: Relevance
“…Such a new generation of self-assembling protein-only nanoparticles appears as a paradigmatic example of an active targeting strategy because of its high cell specificity and its outstanding biodistribution selectivity. This has been further confirmed when using this material to transport different biological or chemical drugs, showing a highly selective cytotoxic effect in CXCR4+ target cells [ 12 , 35 , 36 , 37 , 38 , 39 ]. In fact, T22-GFP-H6 nanoparticles show high clinical relevance as a drug delivery system.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Such a new generation of self-assembling protein-only nanoparticles appears as a paradigmatic example of an active targeting strategy because of its high cell specificity and its outstanding biodistribution selectivity. This has been further confirmed when using this material to transport different biological or chemical drugs, showing a highly selective cytotoxic effect in CXCR4+ target cells [ 12 , 35 , 36 , 37 , 38 , 39 ]. In fact, T22-GFP-H6 nanoparticles show high clinical relevance as a drug delivery system.…”
Section: Introductionmentioning
confidence: 73%
“…In this regard, its covalent binding with the genotoxic antimetabolite Floxuridine (FdU) efficiently and selectively eliminates CXCR4+ cancer stem cells, thus preventing metastases and also inducing the regression of already stablished metastases with no toxicity in non-target tissues [ 35 ]. In a similar approach, its covalent binding with Monomethyl auristatin E, a potent tubulin inhibitor, selectively eliminates CXCR4+ leukemic cells showing potent antineoplastic activity in an acute myeloid leukemia animal model [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Freshly isolated MSCs have a good homing effect, which is decreased after somatic expansion. For example, the chemokine receptor CXCR4 is highly expressed on primary bone marrow MSCs, but gradually lost with passages, resulting in the less recognition of its ligand CXCL12 (also known as SDF-1α) [ 74 , 75 ]. Together, the primary MSCs are expected to have a better therapeutic efficacy due to more potent migration capacity.…”
Section: Challenges In Technology Transfer Of Mscs From Bench To Bedsmentioning
confidence: 99%
“…Similarly, the novel MEF2D-BCL9 fusion transcript identified by RNA-seq was found to increase HDAC9 (histone deacetylase 9) expression and to enhance the resistance to dexamethasone in acute lymphocytic leukemia (ALL) [124]. Leukemia stem cells (LSCs), a rare cell population assumed to be responsible for relapse, is crucial to improve the prognosis of patients [125,126]. RNA-seq analysis showed that LSCs have a unique lncRNA signature with functional relevance and therapeutic potential, providing an explanation for chemotherapy resistance and disease recurrence [127].…”
Section: Cancer Drug Resistancementioning
confidence: 99%